Epidemiology of male urethral strictures in Pakistan - Abidi, Syed Saeed; Gazder, Tanzeel; Manzoor Hussain; Syed Rabiullah; Mazahir Zulfiqar; Rizvi, Syed Adibul Hasan (Journal of the Pakistan Medical Association, 2023)
Urethral stricture disease is relatively common in Pakistan, constituting 4-5% of the urological workload. Despite the high prevalence, little is known about its epidemiology in the country. The current narrative review comprised search on PubMed, Pak MediNet and Google Scholar databases for studies done in Pakistan and published between January 1, 2000, and December 31, 2021. The search yielded 30 local publications on stricture urethra. Demographic data as well as causes and management pattern of male urethral stricture were noted and analysed. There were 5,021 patients, with 3850 (76.6%) being from the province of Sindh. The disease was in majority impact younger patients aged up to 40 years n=1572, while after the age of 60 years, 248 (9%) patients had the disease. The common cause was trauma due to road traffic accidents in both anterior and posterior strictures compared to idiopathic cause reported in the West. ---Continue